Perceived Brand Globalness/Localness: A Systematic Review of the Literature and Directions for Further Research. Issue 1 (March 2021) - Liu, Hao; Schoefer, Klaus; Fastoso, Fernando; Tzemou, Efstathia
Extensive research has investigated how perceived brand globalness (PBG) and perceived brand localness (PBL) affect brand. In this systematic literature review, the authors organize and synthesize the literature on PBG and PBL by analyzing 95 articles published in the past 17 years. They identify similarities, inconsistencies, and omissions in the literature by investigating different conceptualizations of PBG and PBL, boundary conditions of PBG and PBL effects on brand preference, psychological mechanisms through which PBG and PBL affect brand preference, the theoretical foundations underlying PBG and PBL research, and methodological approaches used in the literature. The study outlines avenues for further research based on prior research and current global trends, such as hybridization/glocalization marketing strategies, antiglobalization trends, and digitalization.